Global economic effects of the Asian currency devaluations - Noland, Marcus; Liu, Li-Gang; Robinson, Sherman; Wang, Zhi (Institute for International Economics, 1998)
This study quantifies the impact of the currency changes on the individual countries in Asia, on the United States, on Europe and on other regions on a sector-by-sector basis. It analyzes the additional impact that might occur if China were to devalue its currency as well. It then examines potential trade policy responses to these developments including the risk of an upsurge in protectionist pressure in the United States